Education Disruption and Its Long-Term Societal Impact in Yemen (2015–2026) - Maher Asaad Baker; Fuad Al-Qrize (Mahogany Journal De Social, 2026)
This study examines how Yemen’s long-running conflict has disrupted education and the lasting social effects. War and economic collapse have forced millions of children out of school and destroyed schools. Our goal is to measure these impacts using available data and remote methods. We gathered reports from UN agencies, NGOs, news, social media, and interviews with Yemenis abroad. We used both manual review and AI (LLMs) to analyze themes. Key findings show dramatic enrollment declines (now roughly 42% of young people enrolled), 4–5 million children out of school, and severe teacher attrition (over 65% of teachers unpaid). These losses risk a “lost generation” of uneducated youth. The paper highlights consequences like rising child marriage, child labor, and future economic drag if education isn’t restored. It calls for flexible, conflict-sensitive education programs and better remote monitoring tools. This analysis adds context with latest data and suggests urgent actions.